The association of home quarantine during the Covide-19 pandemic on the lifestyle and mental wellbeing of citizens in Jordan - M. Al-Nawaiseh, Ali; Kilani, Hashem; F. Bataineh, Mo’ath; Atiyat, Khaled; Al-Kilani, Maher; Mansi, Tayseer; Jaber, Ruba; Swidan, Ahmad (Dirasat: Human and Social Sciences, 2022)
During the COVID-19 pandemic a home confinement was enforced in Jordan, We investigated the physical activity, dietary status and sleep quality and mental wellbeing during the lockdown, A sample of Jordanian adults (N =1088, 18-65 Years Old) answered the survey which employed the use of the following tools to conduct information:1- Food Frequency Questionnaire (FFQ), 2- International Physical Activity Questionnaire (IPAQ), 3- WHO-5 Mental wellbeing score, and 4- Pittsburgh Sleep Quality Index (PSQI). Participants of the study (565 females and 523 males) who completed the online survey consented to answer the survey questions after being assured that all their responses will be kept unanimous and no questions will reveal their identity. Statistical analysis (ANOVA) showed differences in the mental wellbeing index according to the physical activity level (F (2, 1087) = 49.181; P <0.0001). T-test also showed that there was a significant difference in the mental wellbeing index according to sleep quality (t = (1086) = -13.476; P <0.0001), and participants’ nutritional status (t = (1086) = -6.078; P <0.0001). Pearson correlation coefficient analysis indicated significant positive relationship between mental wellbeing and daily physical activity level (r = 0.324; P) <0.0001). Furthermore, results revealed that mental wellbeing was negatively correlated with sleep quality (r = -0.419; P <0.0001) and noticed to be higher among participants with better dietary status (r = 0.255; P <0.0001). It is concluded that enhancing nutritional status and increasing physical activity are keys to maintain mental wellbeing during home confinement associated with the Corona pandemic